2018
DOI: 10.1186/s12864-018-5234-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of novel conserved RNA structures in Drosophila

Abstract: BackgroundComparative genomics approaches have facilitated the discovery of many novel non-coding and structured RNAs (ncRNAs). The increasing availability of related genomes now makes it possible to systematically search for compensatory base changes – and thus for conserved secondary structures – even in genomic regions that are poorly alignable in the primary sequence. The wealth of available transcriptome data can add valuable insight into expression and possible function for new ncRNA candidates. Earlier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…H/ACA-box snoRNAs, in contrast, typically fold into double stem loop structures with the H-box in between and the ACA-box on the 3’end of the exterior loop. This difference in recall has also been observed in previous screens with RNAz ( 50 , 51 ). The detection of box C/D snoRNA genes thus cannot rely on secondary structure predictions alone, calling for specialized tools ( 52 ).…”
Section: Resultssupporting
confidence: 84%
“…H/ACA-box snoRNAs, in contrast, typically fold into double stem loop structures with the H-box in between and the ACA-box on the 3’end of the exterior loop. This difference in recall has also been observed in previous screens with RNAz ( 50 , 51 ). The detection of box C/D snoRNA genes thus cannot rely on secondary structure predictions alone, calling for specialized tools ( 52 ).…”
Section: Resultssupporting
confidence: 84%
“…We also evaluated the presence of conserved structural motifs using CMfinder [46], a software that uses an expectation maximization algorithm that allows to compare secondary structures independently from sequence alignment. A recent study has shown that its sensitivity is optimal in the low conservation range, finding 1/ 3 of the conservation structures when identity is <60% [47].…”
Section: Structural Conservation Of Syntenic Lncrnasmentioning
confidence: 99%
“…We used this software to compare the secondary structures of lncRNAs, intergenic regions and rRNAs, the two later used as negative and positive controls respectively. We first computed the secondary structures individually for each sequence using the RNAfold software from the Vienna Package 2.0 with default parameters [47]. The secondary structures computed with RNAfold were used as input for beagle.…”
Section: Classification Of Lncrna Into Secondary Structure Based Famimentioning
confidence: 99%
“…RNA populates a heterogeneous ensemble of conformations, and the goal of most prediction tools is to differentiate the native structure from its numerous subpopulations [ 66 ]. Second, across species, coding regions contain many structurally conserved elements [ 59 , 67 69 ], which can be used to infer both function and structure. Based on these assumptions, many tools have been established with algorithms designed to identify the minimum free energy (MFE) structure with consideration of conserved motifs, temperature, ion concentrations, and sequence-based properties.…”
Section: In Silico Tools For Assessing the Effect Of Synonymous Varia...mentioning
confidence: 99%